Obesity status is a risk factor for secondary surgery after neurolysis, direct nerve repair or nerve grafting in traumatic brachial plexus injury: A retrospective cohort study - Pichitchai Atthakomol (2020)
© 2020 The Author(s). Background: The objective of the study was to investigate the association between obesity and the presence of secondary surgery following neurolysis, direct nerve repair, or nerve grafting in patients with traumatic brachial plexus injury. Methods: In this retrospective chart review spanning two Level I medical centers in a single metropolitan area, 57 patients who underwent neurolysis, direct nerve repair, or nerve grafting for brachial plexus injuries between 2002 and 2015 were identified. Risk regression analysis was used to evaluate the association between obesity status and secondary surgery. Results: After controlling for the confounding variables of age, high energy injury, associated shoulder dislocation and associated clavicle fracture using multivariate regression (risk regression), the risk ratio of secondary surgery in obese patients compared to non-obese patients was 6.99 (P = 0.028). The most common secondary surgery was tendon or local muscle transfer. Conclusions: There is an increased risk of secondary surgery in obese patients compared to non-obese patients of the same age and with the same severity of injury. The increased risk may be due to challenges related to powering a heavier upper extremity. A weight reduction program might be considered as part of the preoperative strategy.